Severe pneumonia and sepsis caused by dialister pneumosintes in an adolescent - Kaiser, Maximilian; Weis, Meike; Kehr, Katharina; Varnholt, Verena; Schroten, Horst; Tenenbaum, Tobias (Pathogens, 2021)
Background: Dialister pneumosintes (D. pneumosintes) is known to cause dental, periodontal or sinus infections. To date, the pathogen has only been described in a small number of cases with a severe infection. Case report: We describe the clinical case of a 13-year-old, obese female patient that presented with acute respiratory failure and sepsis. A CT-scan showed extensive bilateral patchy areas, subpleural and peribronchovascular consolidations with surrounding ground-glass opacity, extensive consolidations in the lower lobes of both lungs matching to a severe pneumonia and clinically emerging acute respiratory distress syndrome. Moreover, it showed extensive sinusitis of the right sinus frontalis, maxillaris and right cellulae ethmoidales. D. pneumosintes was isolated from an anaerobic blood culture obtained at admission. The antibiotic treatment included piperacillin/tazobactam and oral switch to ampicillin/sulbactam plus ciprofloxacin. Conclusions: We describe the first adolescent with severe systemic D. pneumosintes infection. Since the pathogen is difficult to culture the systemic virulence remains unclear. This work aims to sensitize health care specialists to consider D. pneumosintes infection in patients with periodontal or sinusal infection.
Gesehen am 05.10.2021